Time to initiation of antiresorptive agents in multiple myeloma to reduce skeletal related events - Bhasin, Amman; Binder, Adam Finn; Damron, Leland; Majeed, Amry; Barsouk, Adam; Hughes, Kelly; Raj, Niketa; Abdulkareem, Abdullateef O.; Zhan, Tingting; Polu, Divya; Gundepalli, Sai; Devarakonda, Srinivas (Frontiers in Hematology, 2025)
PurposeCurrent treatment guidelines strongly support the use of antiresorptive therapy in patients with newly diagnosed multiple myeloma (NDMM) with the goal of preventing skeletal related events (SRE). Despite these concrete, data-driven recommendations, the impact of delays in antiresorptive initiation in NDMM patients is understudied. Through a multicenter retrospective study, we examined the impact of delays in antiresorptive initiation on the rates of SREs. We furthered our exploration of this topic in a separate retrospective analysis with a focus on reasons for delays in antiresorptive therapy initiation.MethodsElectronic health records from two large academic institutions were used to identify patients with NDMM between July 1, 2016, and June 30, 2019. Exclusion criteria included patients with previous antiresorptive use and patients never prescribed antiresorptives. Time to antiresorptive initiation and its subsequent impact on the rate of SREs was analyzed using hazard ratios. A follow up, single-center retrospective study was conducted using EHR data with an emphasis on the identification of barriers to antiresorptive initiation. Here, descriptive, and inferential statistics were used to identify variables that have a statistically significant impact on antiresorptive initiation.ResultsA total of 759 patients with newly diagnosed MM met inclusion criteria for our multicenter study. Our study found that a delay in initiation of anti-resorptive therapy of greater than 31 days from diagnosis resulted in an increased risk for SRE with a hazard ratio of 1.654 (95% CI: 1.054-2.598; p-value = 0.029). In our follow up study, a total of 45.6% of patients with newly diagnosed MM were prescribed antiresorptive therapy, while 59% of patients with identified lytic lesions on screening imaging received anti-resorptive therapy. Statistically insignificant differences were observed in the time to initiation of anti-resorptive therapy based on health insurance. Variables such as race and gender were not found to have a statistically significant relationship with delays in antiresorptive initiation.ConclusionsPatients with NDMM should be initiated on antiresorptive therapy without delay to minimize the rates of SREs, and clinicians should be diligent in anticipating delays in initiation such as need for dental clearance and renal disease.